A register-based 13-year to 43-year follow-up of 70 patients with obsessive–compulsive disorder treated with capsulotomy. Issue 5 (6th June 2017) - Rück, Christian; Larsson, Johan K; Mataix-Cols, David; Ljung, Rickard
Abstract : Objectives: Little is known about the long-term medical status of patients with severe obsessive–compulsive disorder (OCD) undergoing capsulotomy, a neurosurgical last-resort treatment. The present study used national registers to identify all operated patients with OCD in Sweden and evaluated their long-term medical status, including mortality, hospital admissions and psychotropic medication after capsulotomy for OCD. Design: Register-based long-term follow-up cohort study. Participants: We used the procedural and diagnostic codes in the Swedish National Patient Register to define the study population between 1970 and March 2013. Verification by manual review of medical records of the indication for surgery in those identified by the register yielded the final study cohort of 70 patients, followed 13–43 years after surgery. The sensitivity of the case selection method was 86%. Outcome measures: We studied hospitalisation 5 years before and after surgery. Mortality data were derived from the Causes of Death Register. The Prescribed Drug Register was used to study psychotropic drug utilisation. Results: By March 2013, 29 of the 70 patients were deceased. Their mean age at the time of death was 68 years (SD=14). Two patients had committed suicide and one had died of suspected suicide. Seventy per cent had been admitted to a psychiatric ward in the 5 years preceding surgery, and 84% in the first five postoperative years. Seventy-five per cent of those alive in 2012 were prescribed at least two psychotropic medications, often at high doses, the most common being antidepressants. Conclusions: Malignant OCD has a poor long-term prognosis. Patients who are candidates for surgery should be informed that, while OCD symptoms may be ameliorated with surgery, they should not expect long-term freedom from medication and psychiatric care.